1989
DOI: 10.1007/bf00269048
|View full text |Cite
|
Sign up to set email alerts
|

In vitro shoot regeneration of Populus deltoides: effect of cytokinin and genotype

Abstract: Treatment differences were observed in the in vitro adventitious shoot regeneration response from internodal explants of three genotypes of Populus deltoides cultured on media supplemented with five concentrations each of the cytokinins 6-benzyladenine, 2-isopentyladenine, and zeatin. For each of the three genotypes, the greatest number of shoots were consistently regenerated on media containing the cytokinin zeatin. Tissue necrosis resulted when explants from any of the three genotypes were cultured on media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Therefore, multiplication experiments were carried out after six subculture cycles. Our findings are in corroboration with findings of workers where genotypic variations were encountered in the in vitro indices during culture multiplication phase (AHUJA, 1983;COLEMAN and ERNEST, 1989).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, multiplication experiments were carried out after six subculture cycles. Our findings are in corroboration with findings of workers where genotypic variations were encountered in the in vitro indices during culture multiplication phase (AHUJA, 1983;COLEMAN and ERNEST, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…Variability in the responses of clones and their reactivity to different steps of micropropagation (establishment, proliferation, rooting) has been demonstrated in Pinus radiata by HORGAN (1987). In addition, AHUJA (1983), COLEMAN and ERNEST (1989) reported that shoot regeneration ability of different Populus clones (hardwood) is genotype dependent. Apart from shooting and rooting ability, differences in patterns of proliferation under in vitro environment have been reported in case of Eucalyptus hybrids (SHARMA and KALIA, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…BA also showed toxic effects when it was used to induce shoot formation from callus. Although BA is widely used in tissue culture of Populus (Park & Son 1988;Russell & McCown 1988;Sellmer & McCown 1989;De Block 1990), toxicity has been reported (Coleman & Ernst 1989).…”
Section: Discussionmentioning
confidence: 99%
“…There are many publications which describes the obtaining tissue cultures, clonal micropropagation and regenerants of poplar [19][20][21][22][23][24]. Protocols for induction of regenerants are described also in many articles devoted to genetic transformation of poplars.…”
Section: Introductionmentioning
confidence: 99%